Pemanfaatan Digitalisasi Dalam Promosi Makanan Khas dan UMKM Lokal Daerah Pali Berbasis Web - Hidayat, Kemas Muhammad Wahyu (Jurnal Nasional Ilmu Komputer, 2024)
Digitalization has become a crucial element in supporting the development of local Micro, Small, and Medium Enterprises (MSMEs), particularly in facing the challenges of the globalization era. PALI Regency, with its diverse culinary traditions and potential for local MSMEs, requires digital-based promotional innovations to increase competitiveness and expand its market. This study aims to develop a web-based promotional system for local MSMEs and traditional foods by applying the Waterfall software development method. This method involves the stages of needs analysis, system design, implementation, testing, and maintenance, which are applied sequentially to ensure optimal results. The needs analysis stage is carried out by identifying user needs through surveys and interviews with MSMEs, as well as literature analysis. The system design focuses on user experience (UX) to facilitate user access to display products and related information. During the implementation stage, the system was built using modern web technology that supports responsiveness and speed of access. Testing was conducted to ensure all features function properly, followed by user evaluation to obtain constructive feedback. The results show that this web-based platform can significantly increase the visibility of PALI local products. This system makes it easier for consumers to access product information and conduct online transactions. With promising results, further development is proposed to add features such as digital payment integration and analytics-based sales data reporting. This study concludes that utilizing web-based digitalization through a waterfall approach can be an effective solution for promoting local specialty foods and MSMEs, while simultaneously supporting sustainable regional economic growth